Higher Prostate Weight Is Inversely Associated with Gleason Score Upgrading in Radical Prostatectomy Specimens - Leonardo Oliveira Reis; Emerson Luis Zani; Leandro L. L. Freitas; Fernandes Denardi; Athanase Billis (Advances in Urology)
Background. Protective factors against Gleason upgrading and its impact on outcomes after surgery warrant better definition. Patients and Methods. Consecutive 343 patients were categorized at biopsy (BGS) and prostatectomy (PGS) as Gleason score, ≤6, 7, and ≥8; 94 patients (27.4%) had PSA recurrence, mean followup 80.2 months (median 99). Independent predictors of Gleason upgrading (logistic regression) and disease-free survival (DFS) (Kaplan-Meier, log-rank) were determined. Results. Gleason discordance was 45.7% (37.32% upgrading and 8.45% downgrading). Upgrading risk decreased by 2.4% for each 1 g of prostate weight increment, while it increased by 10.2% for every 1 ng/mL of PSA, 72.0% for every 0.1 unity of PSA density and was 21 times higher for those with BGS 7. Gleason upgrading showed increased clinical stage (P=0.019), higher tumor extent (P=0.009), extraprostatic extension (P=0.04), positive surgical margins (P<0.001), seminal vesicle invasion (P=0.003), less “insignificant” tumors (P<0.001), and also worse DFS, χ2=4.28, df=1, P=0.039. However, when setting the final Gleason score (BGS ≤6 to PGS 7 versus BGS 7 to PGS 7), avoiding allocation bias, DFS impact is not confirmed, χ2=0.40, df=1, P=0.530.Conclusions. Gleason upgrading is substantial and confers worse outcomes. Prostate weight is inversely related to upgrading and its protective effect warrants further evaluation.